Faktor-Faktor Yang Mempengaruhi Keputusan Petani dalam Pemilihan Komoditas (Studi Kasus Pada Tanaman Tembakau dan Padi Di Kabupaten Pamekasan) - Mardiyah Hayati; Siti Maisaroh (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2019)
Tobacco is one of the commodity of fams contributing to the foreign exchange of the country. However, tobacco development, in other side, obtain obstacles by promoting anti-cigar tremendously ditermined in various countries including Indonesia. It is affected to tobacco sales of farmers. With the result that farmers decrease the amount of their production or they change into another commodity. This study is conducted to find out the factors influencing of farmers decision commodities selection in Durbuk, Pademawu, Pamekasan. Furthermore, the study is tofind out the distinction income of tobacco farmers and oryza farmers. Furthermore, this study is to find out The data used in this study is primary data. Independent T-test and logistic binary regression are used as the instrument. The result represent that the factors influencing to farmers’ decision commodities selectionare the large of field and experience and there is difference between the income of tobacco farmers and rice plant farmers. So that, the emphasizing strategy is done by socializing to increase tobacco farmers in order that farmers be more responsive nevertheless it has high risk in condition smart farmers with exact plan schedule